2008
DOI: 10.1016/j.jfms.2007.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Guarded long-term prognosis in male cats with urethral obstruction

Abstract: The aim of this study was to evaluate the course of urethral obstruction in cats. Forty-five male cats with urethral obstruction or lower urinary tract signs referable to urethral obstruction were included in the study. Follow-up information was gained by telephone interview in most cases and was available in 39 cats. Of the 22 cats with idiopathic urethral obstruction, eight (36%) re-obstructed after 3-728 days (median 17 days). Of 10 cats with urolithiasis, three (30%) re-obstructed after 10, 13 and 472 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
135
8
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(165 citation statements)
references
References 15 publications
13
135
8
9
Order By: Relevance
“…The overall success rate in the present study (11/15) was lower than the reported survival rate associated with standard treatment of cats with UO (91% to 94% 1,12 ). In addition, given the minimalist approach to treatment dictated by this protocol, we excluded the sickest patients, including cats with profound physiologic and metabolic derangements.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The overall success rate in the present study (11/15) was lower than the reported survival rate associated with standard treatment of cats with UO (91% to 94% 1,12 ). In addition, given the minimalist approach to treatment dictated by this protocol, we excluded the sickest patients, including cats with profound physiologic and metabolic derangements.…”
Section: Discussioncontrasting
confidence: 84%
“…Although it has generally been accepted that the physical presence of a mucous plug or calculus within the urethra plays a primary role in the pathogenesis of UO, 9–11 a recent study 12 found that the cause was idiopathic in > 50% of cats and that urolithiasis and urethral plugs were less common (29% and 18%, respectively, of affected cats). In addition, urethral spasm and edema have been shown to play an important role in UO.…”
mentioning
confidence: 99%
“…Από το 1990 και μετά παρατηρήθηκε ελάττωση της συχνότητας των ουρη-θροστομιών των γάτων στις ΗΠΑ και στον Καναδά, η οποία φαίνεται να συμβαδίζει με τη μείωση της συχνότητας των εμφράξεων της ουρήθρας, λόγω συγ-κριμάτων ή ουρολίθων (Lekcaroensuk et al 2002, Smith 2002. Επισημαίνεται ότι η ΠΟ προλαμβάνει ή αντιμετωπίζει την έμφραξη της ουρήθρας αλλά δεν μπορεί να επηρεάσει τη συχνότητα υποτροπής της μη αποφρακτικής μορφής της νόσου της κατώτερης ουρο φόρου οδού (Smith 2002, Gerber et al 2008. Προ ϋποθέσεις για μια επιτυχημένη ΠΟ αποτελούν: 1) η δημιουργία της στομίας στην πυελική μοίρα της ουρή θρας μπροστά από τους βολβουρηθραίους αδένες, εκεί όπου η ουρήθρα είναι σημαντικά ευρύτερη σε σχέση με την πεϊκή μοίρα, 2) η απελευθέρωση του πέους από τις προσφύσεις του με την πύελο έτσι ώστε να ελαχιστοποιηθεί η τάση στη στόμια και 3) η πολύ καλή συμπλησίαση της ουρήθρας με το δέρμα, έτσι ώστε η επούλωση της στομίας να γίνει κατά πρώτο σκοπό και να μειωθεί η πιθανότητα δημιουργίας ουλώδους ιστού και κατά συνέπεια εμφάνισης μετεγ χειρητικής στένωσης (Scavelli 1989, Flanders andHar vey 1994).…”
Section: ιστορική εξέλιξη της ουρηθροστομίαςunclassified
“…A antibioticoterapia tem sido utilizada não somente para as cistites bacterianas (ITU), mas também como profilaxia nos casos em que se utilizam cateteres urinários por 48 a 72 horas, após desobstrução uretral (GERBER et al, 2008). Porém, na ausência de bacteriúria em urinálise, a antibioticoterapia é relativamente contra-indicada enquanto o cateter urinário estiver em vigor, sendo indicada apenas após a sua retirada (RIESER, 2005).…”
Section: Antibioticoterapiaunclassified
“…Esses animais toleram bem o pós operatório e tem boa qualidade de vida em longo prazo (CORGOZINHO et al, 2007). Gerber et al (2008) afirmam que o prognóstico é reservado, pois os sinais clínicos e a obstrução uretral (independente da causa) podem recorrer, visto que a cirurgia apenas corrige a obstrução uretral, e não a doença subjacente, necessitando continuidade da terapia medicamentosa ou dietética instaurada (CORGOZINHO et al, 2007;GERBER et al, 2008;WILLIAMS, 2009).…”
Section: Antibioticoterapiaunclassified